Analisis Faktor yang Mempengaruhi Ketepatan Waktu Pelaporan Keuangan pada masa covid-19 - Brian Mahadika Putra Bambang Supriyanto (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
This research is to see, test, and analyze the factors of profitability, liquidity, company size, company age and reputation of public accounting firms (KAP) that affect the timeliness of financial reporting during the Covid-19 pandemic. This type of research is quantitative research, the population in this study uses manufacturing companies listed on the Indonesia Stock Exchange during 2019-2021. The sample was taken using a purposive sampling technique by obtaining data on about 574 out of 595 total manufacturing companies that fit the research criteria. The data analysis technique used is the logistic regression coefficient. Based on the results of the study, it shows that profitability, company size, company age have no positive and significant effect on the timeliness of financial reporting, and KAP reputation has no negative and significant effect on the timeliness of financial reporting. while liquidity has a positive and significant effect on the timeliness of financial reporting